2018
DOI: 10.1021/acs.jafc.8b01655
|View full text |Cite
|
Sign up to set email alerts
|

Glyphosate Resistance Technology Has Minimal or No Effect on Maize Mineral Content and Yield

Abstract: Controversy continues to exist regarding whether the transgene for glyphosate resistance (GR) and/or glyphosate applied to GR crops adversely affect plant mineral content. Field studies were conducted in 2013 and 2014 in Stoneville, MS and Urbana, IL to examine this issue in maize. At each location, the experiment was conducted in fields with no history of glyphosate application and fields with several years of glyphosate use preceding the study. Neither glyphosate nor the GR transgene affected yield or minera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…Intensive use of glyphosate has been associated with increased resistance in plants, while glyphosate residues are routinely detected along the food production chain and in the environment. The herbicide has been detected in soybeans [9–14], maize [15, 16], canola [17], and poultry and cattle feed [18], as well as in urine samples of humans and cows [19–21]. Data regarding the amount of residues vary depending on the time of harvest, particular pesticide regulations in different countries, and the applied formulation.…”
Section: Introductionmentioning
confidence: 99%
“…Intensive use of glyphosate has been associated with increased resistance in plants, while glyphosate residues are routinely detected along the food production chain and in the environment. The herbicide has been detected in soybeans [9–14], maize [15, 16], canola [17], and poultry and cattle feed [18], as well as in urine samples of humans and cows [19–21]. Data regarding the amount of residues vary depending on the time of harvest, particular pesticide regulations in different countries, and the applied formulation.…”
Section: Introductionmentioning
confidence: 99%
“…Although qualification of the traces of Gly in cane fiber, cane roots, as well as cane shoot was not involved in this study, studies on the persistence of Gly in crops revealed that the accumulation of Gly in these parts of a crop was below the limit of detection [40][41][42]. More interestingly, application of GLy on sugar beet only found trace amounts of glyphosate residue in its shoots and roots during two weeks' treatment [43]. As shown in Table 3, all cane juice from the Gly-sprayed experiments had its residue in a range of 1.05 to 1.06, which is under the limit as per the regulations of the Ministry of Health (Gly ≤ 2 µg/mL).…”
Section: Evaluation Of Ga3 and Gly Residues In Sugarcanementioning
confidence: 80%
“…We also found no reductions in yield by glyphosate application on GR corn or GR soybean in fields with a long history of glyphosate use or with no history of glyphosate use [50, 51]. In a similar study with GR sweet corn, there was even a slight increase in yield associated with glyphosate application [52], which could have been due to hormesis, a phenomenon with non-phytotoxic doses of glyphosate [53].…”
Section: Discussionmentioning
confidence: 98%